DOI: 10.18174/459150
|View full text |Cite
|
Sign up to set email alerts
|

Phthalates mixtures in bottled water in Iran: human health risk assessment using direct and indirect exposure assessment

Abstract: Chapter Magnetic solid-phase extraction based on modified magnetic nano-particles for the determination of phthalate diesters in water samples……. …………………….….. 75 Chapter Concentrations of phthalates in bottled water under common storage conditions:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 294 publications
(442 reference statements)
0
1
1
Order By: Relevance
“…The levels of phthalates recorded in this study is however signi cantly higher than the levels reported in bottled water globally and in Ghana (Zaater, Tahboub and Al Sayyed, 2014;Jeddi, 2018). This trend could be attributed to the difference in the polarities of the various extemporaneous preparations.…”
Section: Discussioncontrasting
confidence: 81%
“…The levels of phthalates recorded in this study is however signi cantly higher than the levels reported in bottled water globally and in Ghana (Zaater, Tahboub and Al Sayyed, 2014;Jeddi, 2018). This trend could be attributed to the difference in the polarities of the various extemporaneous preparations.…”
Section: Discussioncontrasting
confidence: 81%
“…However, due to their nature, phthalates can easily migrate from plastic materials into drinking water, or beverages during production and storage [17][18][19]. The migration of PAEs' depends on their concentrations in the packaging polymer, the acidity of content in contact with packages, and the lipid content [20][21][22][23]. Dimethyl phthalate (DMP), Diethyl phthalate (DEP), Dibutyl phthalate (DBP), Benzyl butyl phthalate (BBP), Di-(2-ethylhexyl) phthalate (DEHP), Di-n-octyl phthalate (DnOP), Di-iso-nonyl phthalate (DiNP), and Di-iso-decyl phthalate (DiDP) are most commonly used in industry as plasticizers [24,25].…”
Section: Introductionmentioning
confidence: 99%